Radiological CT Patterns and Distribution of Invasive Pulmonary Aspergillus, Non-Aspergillus, Cryptococcus and Pneumocystis Jirovecii Mold Infections – A Multicenter Study - Obmann, Verena C.; Bickel, Flurina; Hosek, Nicola; Ebner, Lukas; Huber, Adrian T.; Damonti, Lauro; Zimmerli, Stefan; Christe, Andreas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Clinical signs and symptoms related to invasive fungal disease are nonspecific and need to be followed up by appropriate diagnostic procedures. The goal of this study was to analyze CT imaging patterns in invasive fungal infections and their correlation with the immune status and clinical outcome.Materials and Methods We performed a retrospective multicenter study including 85 consecutive patients with invasive pulmonary fungal infection (2011–2014). Lung patterns on computed tomography (CT) scans were classified according to the Fleischner Society glossary. The patients were grouped according to immune status (neutropenia, steroid therapy, organ transplant recipient, and other cause) and outcome (positive outcome, progressive disease, and death). The Chi square test or Fisher exact test was used. Bonferroni correction was applied.Results The total number of patients with invasive Aspergillus and non-Aspergillus infection (IANA), Pneumocystis jirovecii pneumonia (PCP), and Cryptococcus (CRY) was 60, 22, and 3, respectively. Patients with IANA demonstrated significantly more nodules (93 % vs. 59 %, p = 0.001), significantly fewer ground glass opacities (58 % vs. 96 %, p = 0.005), and significantly fewer positive lymph nodes (5 % vs. 41 %, p < 0.001) than patients with PCP. All patients with PCP and CRY had a favorable outcome. Patients with IANA and an adverse outcome demonstrated significantly more nodules with halo sign than patients with IANA and a favorable outcome (42.5 % vs. 15.9 %, p < 0.0001). Interestingly, patients with IANA and a favorable outcome had a higher prevalence of pulmonary infarction than patients with an adverse outcome (8 % vs. 1 %, p = 0.047). Patients with neutropenia showed significantly more consolidations (66 %) than organ transplant recipients (27 %, p = 0.045).Conclusion Patients with IANA showed a higher prevalence of nodules and a lower prevalence of ground glass opacities than patients with PCP. In patients with IANA, nodules with halo sign were associated with an adverse outcome. Patients with neutropenia showed generally more consolidations, but the consolidations were not associated with an adverse outcome.Key Points: Citation Format
Keywords: ultrasound computed tomography (US/CT); x-ray; invasive fungal infections; chest; pneumonia